STRATEGI PERLINDUNGAN ANAK DALAM RANGKA PELAYANAN PUBLIK DI KOTA BANDUNG - Setiawan, Agustina (Jurnal Politikom Indonesiana, 2016)
Abstract The handling of child protection has not been established in Bandung in common a view over the issues of children's rights, resulting in differences in the understanding of the needs and treatment strategies. This is evident from the handling of the problem of children who have not run optimally so that there are still many problems in handling. This study used a descriptive research method with a qualitative approach, the data used will be more complete, in-depth and reliable. Given the difficulties faced by the city government such as the prevention and handling of child abuse, exploitation, mistreatment and neglect of children. Children who do not get good service by parents that children behave become street children, children who are dealing with the law, child deviant behavior such as sex, drinking and drugs as part of the mismanagement of the parents. Many children are not getting proper education, proper health and do not have lands a decent playground. The number of street children in Bandung, which reached 2,162 children , abandoned children who reach 5,848 poor children and children's children who reach 78 751 in 2012 . Lack of optimal handling of the child by the local government led to the growth of street children and poor children increased in Bandung, supported by a low awareness of the public led to the increasing problem of child protection. Necessary measures to prevent and deal with perlinidungan children through role local government and the community to seriously address the issue of child protection. One effort is the implementation of the model and the right strategy so that the child can be humanized and disejahterakan through a model of prevention and protection of children's snacks. The child protection strategy includes: 1 ) prevention through awareness building society , making policies , involving the community, institutional and service delivery . 2 ) treatment through the identification of child problems , withdrawal , rehabilitation , reintegration and care management . Through the model and this strategy is expected to be upgraded to child protection services in the City of Bandung through the policies formulated by the local government of Bandung .